Diagnostic criteria in invasive pituitary adenomas - Ioana-Maria Moldovan; Carmen Melincovici; Carmen Mihaela Mihu; Sergiu Susman; Anne-Marie Constantin; Stefan Ioan Florian (Romanian Neurosurgery, 2016)
Pituitary adenomas are benign pituitary primary tumors, the most frequent type of tumor in the pituitary fossa. An important part, around 1/3 of the pituitary adenomas manifests an aggressive behavior, growing faster and invading into parasellar areas (cavernous sinus, neural tissues and bones). Objectives: the first aim of this paper is to review the last findings about invasiveness diagnostic criteria, imagistic and biomarkers, which can be used in the classification of pituitary tumors and also to predict the probability of invasiveness, tumor recurrence and suspicion of malignancy. The second aim is to highlight the morphological and clinic types of invasive pituitary adenomas. Materials and methods: we performed a systematic review and analysis of the published articles, searching PubMed between January 1985 and December 2015. There were selected articles published in English, reviews and abstracts. During the advanced search type in PubMed, combinations of the following keywords were used: “pituitary adenoma”, “invasive”, “aggressive”, “biomarkers”, “classification”, “histological subtypes”, ‘”immunohistochemical markers”. Results: 215 articles were selected, regarding diagnostic, prognostic and therapeutic aspects. There were some histological subtypes of pituitary adenomas known as having an aggressive clinical behavior. Several biomarkers were identified as being associated with the invasive feature: proliferation markers (Ki-67 index, number of mitoses, p53 & p27 expression, microvascularization density, telomerase, topoisomerase 2 Alpha), matrix metalloproteinases, protein kinase C, cyclooxygenase-2, E-cadherin, transcription Factors, genetic alterations (PTTG gene, Galectin-3 protein/ LGALS3 gene), apoptosis markers. Based on their invasion and proliferation characteristics, pituitary tumors are proposed to be classified into five grades (1a, 1b, 2a, 2b, 3), the grade 2b tumor with high risk of recurrence being considered as tumor suspected of malignancy. Conclusions: Using a set of specific biological markers for invasive process, there is hope to establish an early diagnosis and prevention of invasive pituitary adenomas. Due to the fact that aggressive pituitary tumors are generally difficult to manage, unresponsive to therapy, quickly recurrent and associated with poor prognosis, the early diagnosis and the search for new therapeutic approaches is becoming mandatory. Instead of using “invasive” or “aggressive” adenoma, the term “tumor suspected of malignancy” would be used for more accuracy.